Impact of particulate air pollution on airway injury and epithelial plasticity; underlying mechanisms - Kayalar, Özgecan; Rajabi, Hadi; Konyalilar, Nur; Mortazavi, Deniz; Aksoy, Gizem Tuşe; Wang, Jun; Bayram, Hasan (Frontiers in Immunology, 2024)
Air pollution plays an important role in the mortality and morbidity of chronic airway diseases, such as asthma and chronic obstructive pulmonary disease (COPD). Particulate matter (PM) is a significant fraction of air pollutants, and studies have demonstrated that it can cause airway inflammation and injury. The airway epithelium forms the first barrier of defense against inhaled toxicants, such as PM. Airway epithelial cells clear airways from inhaled irritants and orchestrate the inflammatory response of airways to these irritants by secreting various lipid mediators, growth factors, chemokines, and cytokines. Studies suggest that PM plays an important role in the pathogenesis of chronic airway diseases by impairing mucociliary function, deteriorating epithelial barrier integrity, and inducing the production of inflammatory mediators while modulating the proliferation and death of airway epithelial cells. Furthermore, PM can modulate epithelial plasticity and airway remodeling, which play central roles in asthma and COPD. This review focuses on the effects of PM on airway injury and epithelial plasticity, and the underlying mechanisms involving mucociliary activity, epithelial barrier function, airway inflammation, epithelial-mesenchymal transition, mesenchymalepithelial transition, and airway remodeling.